Peningkatan Efisiensi Energi Menggunakan Baterai Dengan Kendali Otomatis Penerangan Ruang Kelas Berbasis PLTS - Roal, Mario (ELKHA : Jurnal Teknik Elektro, 2015)
Abstract– This paper shows a simulation result from automatic lighting control system prototype. This system using AC voltage source coming from energy supply battery based Solar Power Plants (PLTS). Automatic lighting control system aimed to minimize the energy consumption of the battery use for room lighting lamp by utilizing the light came from outdoor.  The Controller used in this system was microcontroller ATMega16. The Controller system main function was to regulate the use of the lighting lamp in accordance with room by turning on or turning off the light as needed.The system maintained the room illumination light in a range of 250 – 300 lux. This range was based on the Indonesian National Standard (i.e. SNI 03-2396-2001) where the illumination for a classroom was standardized to be 250 lux. The system controlled the battery energy consumption in two way. Firstly, if there were people in the room, then the system would turn on the lighting lamp automatically or vice versa.  Secondly, the system turned on or turned off some lamps by adjusting amount of light entering from the outside room. These calculations were compared the power needed when there is no interfere lighting from outside to the room (classification I) or in this case the control device was not functioning. Average efficiency number of battery energy consumption for 6 hours base on 6 classification load was classification II was 1,48 Watt/hour, classification III was 2,46 Watt/hour, classification IV was 3,65 Watt/hour, classification V was 4,67 Watt/hour, classification VI was 6,3 Watt/hour and classification  VII was 8,59 Watt/hour. Relationship of energy consumption and battery supply endurance was as follows (classification II (6-7 hour), classification III (8-9 hour), classification IV (10-11 hour), classification V (12-13 hour), classification VI (18-19 hour). 10 Wp solar cell was used to recharge battery with a capacity of 5Ah and take 8 requires hours with 1,171 charging current average. Keywords– Battery, automation, led, prototype, solar power plant.